THROMBOTIC THROMBOCYTOPENIC PURPURA RELATED ACUTE MYOCARDIAL INFARCTION - Betül Çavuşoğlu Türker; Süleyman Ahbab; Fatih Türker; Hayriye Esra Ataoğlu (Medico Research Chronicles, 1970)
Introduction: Thrombotic thrombocytopenic purpura (TTP) is a rare life-threatening thrombotic microangiopathy. The central nervous system, kidneys, and myocard can be affected by TTP.Case Presentation: A 47-year-old female patient with no chronic disease came to the emergency department presented with chest pain, blur in seeing. Electrocardiogram was performed and there was biphasic T wave pattern. Laboratory tests showed an elevation in white blood cell (14.103/mm3), decrease in thrombocyte (3.000/mm3). Blood urea nitrogen (BUN) was 129.3 mg/dl, serum creatinine was 1.87 mg/dl, lactate dehydrogenase (LDH) was 1581 U/l. Cardiac markers were elevated. These tests results revealed non ST-elevation myocardial infarction and acute renal injury. Antithrombotic agents were not applied because of thrombocytopenia. ADAMTS 13 activity was found lower than 0, 2 % and ADAMTS 13 antibodies were positive. Plasmapheresis was started to perform, immediately and repeated for ten days. After the treatment, hematologic parameters and LDH values came to normal ranges.Conclusion: Thrombotic Thrombocytopenic Purpura (TTP) is a type of thrombotic microangiopathic anemia. If it is not diagnosed early, the mortality rate can be about 90%. Plasmapheresis should begin immediately.